Longevity cosmeceuticals as the next frontier in cosmetic innovation: a scientific framework for substantiating product claims - Klinngam, Wannita; Chaiwichien, Athit; Osotprasit, Supawadee; Ruktanonchai, Uracha; Kanlayavattanakul, Mayuree; Lourith, Nattaya; Wongrakpanich, Amaraporn; Teeranachaideekul, Veerawat; Iempridee, Tawin (Frontiers in Aging, 2025)
The field of anti-aging research has made remarkable strides with the identification of geroprotectors—compounds capable of extending healthspan and lifespan in animal models—presenting promising implications for human longevity. Building on these advances, we propose a novel product category: longevity cosmeceutical actives and products. Unlike conventional anti-aging products that primarily target superficial signs of aging, longevity cosmeceuticals address the molecular hallmarks of aging, fundamentally enhancing skin health and longevity. To clearly distinguish these scientifically validated products from marketing-driven claims, we define, for the first time, longevity cosmeceutical actives and products based on stringent criteria: (1) they must directly target and modulate established hallmarks of skin aging; (2) they must demonstrably extend “skinspan” over time, reflected by improved skin viability, structure, and functional integrity; and (3) their efficacy must be validated through clinical trials, preferably with post-trial skin biopsies to evaluate aging hallmark biomarkers, along with comprehensive safety assessments. This review explores molecular hallmarks of skin aging, highlights geroprotective compounds with potential cosmeceutical applications, and recommends essential biomarkers for assessing prevention of rapid biological aging. Additionally, we propose methodologies for skinspan assessment and emphasize the importance of robust clinical trial designs. By establishing these scientifically rigorous standards, we aim to drive innovation, substantiate longevity claims, and transform the cosmetic industry toward meaningful biological improvements in skin health.